(untitled) (Journal of Engineering, 2024)
This work deals with the reduction of residual stresses using cryogenic thermal treatment as all alternative to normal thennal treatment .The work was performed on a solid z-shaped model component. Ihe models were fabricated from two difl’erent types of materials (alloy steel & alumin:tm). If any residual stresses exist in a manufactured cornponent, then these residual stresses will have an effect on the natural frequency of that component. A new type of measurement method was used to measure the level of residual stresses present. The nahral frequency of the models at a stress fiee state was used as a reference. This method was also used to find the extent of the residual stress relief and percentage of reduction. Residual stresses were incluced by flame heating with different boundary conditions and at different rates of cooling. They were stress relieved by the use of liquid nitrogen (-198uC) and at different various treatment times. This rvas done to find the effect of time on the treatment. Reduction in residual stress level reached 92.38yo.’firis reduction was compared with a normal thermal stress relief. Also a comparison was macie between the two types of material that were stress relieved. It was found that over treatment tends to re-stress the models.